TCM (Molecular Rapid Test) Examination of Close Contacts of Tuberculosis Patients at RSUD dr H.Chasan Boesoerie - Halwatiah, Halwatiah; Silviani, Yusianti (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Pesticides play a crucial role in maintaining high productivity in the agricultural industry, thus they are considered a vital component of Tuberculosis (TB) is a chronic bacterial infection called Mycobacterium tuberculosis, which can attack organs as the lungs, bones lining of the brain,stomach lining,intestines,lymph nodes and even the urinary tract. The World Organization (WHO) estimate that TB Causesthe deaths of 1,4 million people in the world and around 5.6 million men, 3,2 million women, equal to 130 cases per 100.000 people as of 2019. Transmission of IBC generally occurs through the air. When an active TB sufferer spiashes mucus of phlegm when coughing of sneezing, the TBC bacterial wiil come of tharough the mucus and be carried into the air. The aims of this study was to determine the results of close contact TCM examinations in pulmonary tuberculosis patients at RSUD dr H. Chasan Boesoirie Ternate. This research was conducted at the Chasan Boesoirie Regional hospital, Ternate City.Data obtained from primary data using the observational deskriftive method with a cross secsional study design with purposive sampling technique on 10 patient who were comfirmed positive for TB on TCM.by carring out a TCM examination on close contacts at home, 23 contact were found. Out of 10 TB patient. Based on the reseach result were found on the TCM examination from 23 close contacts of TB patients at RSUD dr. H. Chasan Boesoerie Ternate.It was found that 1 patient in close contact with TB was positive tuberculosis. Keyword: TBC, close household contacts, ICM I examination.